Gambaran Kecerdasan Spiritual Siswa Madrasah Tsanawiyah Negeri 2 Buton: Sebuah Kajian Kualitatif - Rahmanpiu Rahmanpiu; Murni Nia; Muliha Halim; Wa Ode Deli; Harjun Harjun (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to obtain an in-depth understanding of the description of spiritual intelligence among students at madrasah tsanawiyah negeri 2 buton.a qualitative approach with a phenomenological design was employed,enabling the exploration of students' experiences,perceptions,and the meanings of spiritual intelligence from the subjects' own perspectives.data were collected through in-depth interviews,participatory observation,and documentation studies.informants were purposively selected,comprising students from grades vii,viii,and ix,as well as teachers and educational staff.data were analyzed using thematic analysis techniques through stages of data reduction,data presentation,and conclusion drawing.the findings indicate that the spiritual intelligence of mtsn 2 buton students is generally at a sufficiently developed level,reflected in their ability to perceive the learning process as an act of worship,demonstrate self-awareness,exhibit flexibility in facing challenges,and maintain internalized moral values.however,individual variation was observed,influenced by family backgrounds,intensity of religious education,and social environment.these findings underscore the importance of holistic spiritual education in madrasah settings to optimally support students' character development.